MIGHTEE: deep 1.4 GHz source counts and the sky temperature contribution of star-forming galaxies and active galactic nuclei. Issue 2 (18th November 2022) - Hale, C L; Whittam, I H; Jarvis, M J; Best, P N; Thomas, N L; Heywood, I; Prescott, M; Adams, N; Afonso, J; An, Fangxia; Bowler, R A A; Collier, J D; et al.
Abstract: We present deep 1.4 GHz source counts from ∼5 deg 2 of the continuum Early Science data release of the MeerKAT International Gigahertz Tiered Extragalactic Exploration survey down to S 1.4GHz ∼15 μ Jy. Using observations over two extragalactic fields (COSMOS and XMM-LSS), we provide a comprehensive investigation into correcting the incompleteness of the raw source counts within the survey to understand the true underlying source count population. We use a variety of simulations that account for: errors in source detection and characterization, clustering, and variations in the assumed source model used to simulate sources within the field and characterize source count incompleteness. We present these deep source count distributions and use them to investigate the contribution of extragalactic sources to the sky background temperature at 1.4 GHz using a relatively large sky area. We then use the wealth of ancillary data covering a subset of the COSMOS field to investigate the specific contributions from both active galactic nuclei (AGN) and star-forming galaxies (SFGs) to the source counts and sky background temperature. We find, similar to previous deep studies, that we are unable to reconcile the sky temperature observed by the ARCADE 2 experiment. We show that AGN provide the majority contribution to the sky temperature contribution from radio sources, but the relative contribution of SFGs rises sharply below 1 mJy, reaching an approximate 15–25 per cent contribution to the total sky background temperature ( Tb ∼100 mK) at ∼15 μ Jy.